The Influence of Interpersonal Intelligence on PPKN Learning Outcomes of Grade X Students of SMA Negeri 2 Pangkatan, Labuhanbatu Regency - Fitriani, Nur; Adi, Panggih Nur; Saragih, Siti Zahara; Rohana, Rohana (Holistic Science, 2024)
The aim of this research is to determine the influence of interpersonal intelligence on PPKn learning outcomes for class X students at SMA Negeri 2 Pangkatan Kab. Labuhanbatu. The type of research used in this research is quantitative research. Quantitative data was used to see how much influence interpersonal intelligence has on the PPKn learning outcomes of class X students at SMA Negeri 2 Pangkatan Kab. Labuhanbatu. The total population is all class X students of SMA Negeri 2 Pangkatan Kab. Labuhanbatu as many as 157 people. The sampling technique uses a formula from Slovin. Based on the Slovin formula, for a population of 157, and a degree of error d of 0.05, the research sample size was 113 people. Based on the results of data analysis, it can be seen that the correlation coefficient (r) is 0.536 and the determination coefficient (r2) is 0.288. Based on the results of data calculations, it is known that the correlation coefficient is 0.536, this means that the interpersonal intelligence variable (X) has a positive effect on the PPKn learning outcomes of class X students. The better the interpersonal intelligence, the better the PPKn learning outcomes of class Regency. Labuhanbatu